الأخوة على ضوء القرآن والسنة - Nuryana Bt Muhammad Nur (Kolej Universiti Islam Malaysia, 2012)
This research is conducted in order to know the idea of how to glorify the relatives based 011 the Quran and Sunnah. 111 order to find out the information and data needed, the writer uses several methods. Among the methods are library researches by searching the information in the old and modern books. This research is discussed about relationship understanding based on the Quran and Sunnah .The writer discussed also about the problem and effects faced by Muslim in order to form a strong relationship. There important element that have to be inculcated in community formation clarified in this research.The result of this research shows that relationship is important to Muslim for their happiness in this world and hereafter. So, all Muslims are commanded to connect the relationship among them. Therefore, for those who broke the relationship, they will get the hard punishment from Allah whether in this world or hereafter.